Histone variants as emerging regulators of embryonic stem cell identity - Turinetto, Valentina (Epigenetics, 2015)
Dynamic regulation of chromatin structure is an important mechanism for balancing the pluripotency and cell fate decision in embryonic stem cells (ESCs). Indeed ESCs are characterized by unusual chromatin packaging, and a wide variety of chromatin regulators have been implicated in control of pluripotency and differentiation. Genome-wide maps of epigenetic factors have revealed a unique epigenetic signature in pluripotent ESCs and have contributed models to explain their plasticity. In addition to the well known epigenetic regulation through DNA methylation, histone posttranslational modifications, chromatin remodeling, and non-coding RNA, histone variants are emerging as important regulators of ESC identity. In this review, we summarize and discuss the recent progress that has highlighted the central role of histone variants in ESC pluripotency and ESC fate, focusing, in particular, on H1 variants, H2A variants H2A.X, H2A.Z and macroH2A and H3 variant H3.3.